2017
DOI: 10.1021/acsbiomaterials.7b00506
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Delivery of BMP-2-Related Peptide from the True Bone Ceramics/Hollow Mesoporous Silica Nanoparticles Scaffold for Bone Tissue Regeneration

Abstract: Bone morphogenetic protein 2 (BMP-2) is one of the most important factors for bone tissue formation. A number of BMP-2 related small molecule bioactive peptides have been designed and shown to be equally effective in osteogenic activity. In this report, we synthesized a novel BMP-2related peptide (designated P28) and designed a delivery system to regulate the controlled release of P28 from true bone ceramics (TBC) combined with an enlarged pore hollow mesoporous silica nanoparticles (HMSNs) composite scaffold.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 53 publications
(97 reference statements)
2
40
0
1
Order By: Relevance
“…Chemical approaches include incorporation in, and release of biomolecules (e.g., growth factors) from biomaterial carriers. A well-known example is the release of bone morphogenetic protein 2 (BMP-2) to stimulate bone growth [5][6][7], which has obtained market approval. However, biomolecule release from these scaffolds needs to be tightly controlled to avoid initial burst release, potentially causing serious side effects as a result of local supraphysiological concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical approaches include incorporation in, and release of biomolecules (e.g., growth factors) from biomaterial carriers. A well-known example is the release of bone morphogenetic protein 2 (BMP-2) to stimulate bone growth [5][6][7], which has obtained market approval. However, biomolecule release from these scaffolds needs to be tightly controlled to avoid initial burst release, potentially causing serious side effects as a result of local supraphysiological concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…However, biomolecule release from these scaffolds needs to be tightly controlled to avoid initial burst release, potentially causing serious side effects as a result of local supraphysiological concentrations. In addition, uncontrolled biomolecule release minimizes the efficacy as prolonged chemical signalling is not possible [6][7][8]. Next to other approaches using polymers, and microparticles [9][10][11], nanoparticle-based carriers could increase control over the pharmacokinetics of such agents owing to their ability to carry high concentrations of (insoluble) biomolecules, while protecting them from degradation.…”
Section: Introductionmentioning
confidence: 99%
“…But controlling the release of such drugs and growth factors is still a challenge and can be rectied by using carries such as silica nanoparticles. 16,30 Hence validating the incorporation of SiO 2 nanoparticles in hydrogel polymer network which can be 3D printable according to patient's critical defects has immense scope in bone tissue engineering. In this study, we have shown successfully incorporated SiO 2 nanoparticles in a 3D printable hydrogel polymer network and validated the process for patient specic defect 3D printing.…”
Section: Discussionmentioning
confidence: 99%
“…14 A recent study reported that SiO 2 nanoparticles promotes osteo-conduction, improves osteoblast proliferation and induce osteogenic differentiation. 15,16 The release of Si 4+ ions from SiO 2 nanoparticles are also reported to enhance angiogenic ability of human endothelial cells. 17 Hence incorporating silica nanoparticles into alginate and gelatin hydrogels appear to be a promising solution to achieve the required viscosity and mechanical strength for the 3D printed structures.…”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxicity at certain particle sizes and/or concentrations Oh et al, 2005;Raja et al, 2005;Magrez et al, 2009;Lai et al, 2011;Lallana et al, 2012;Portan et al, 2012;Tang et al, 2012;Setyawati et al, 2013;Shadjou and Hasanzadeh, 2015;Zhou et al, 2015;Cui et al, 2018;Tang et al, 2014;Hu et al, 2012;Huang et al, 2014;Kwon et al, 2017;Liu et al, 2017 Organic nanostructured delivery systems Alcantar et al, 2000;Habraken et al, 2007;Lü et al, 2009;Puppi et al, 2010;Anderson and Shive, 2012;Makadia and Siegel, 2011;Jacob et al, 2018 Natural polymers (e.g., gelatin, chitosan)…”
Section: Mimicking Bone's Biochemical Niche: Delivery Of Bioactive Momentioning
confidence: 99%